(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
The Olympic games and sport industry suggest many opportunities for investing and improving. It is also interesting watching how the athletes during the training days prepare for the competition because it includes patience, hard work, and motivation. However, it involves some challenges that can harm the popularity of this competition or it can be connected with the tickets. These issues, incorporate the online ticket shops where some times it is hard to get because of a bad connection or old people won’t be able to take it because they don’t understand how to use the mobile phone and spread all over the world. In addition, there is no places in arena that’s why people sometimes can’t go in and they can loose their money that they paid for competition. The other problem is a crowd because people can be easily robbed their phone, wallet, and cards from bad people. The article will also discuss the history and impact of Olympic games to the world.